Avaliação na atenção básica no interior do Rio Grande do Sul: o olhar da gestão - Souza, Rafaela (2018)
The purpose of this study was to analyze the perception of the municipal health managers of the 19th Regional Health Coordination of Rio Grande do Sul about National Program for Access and Quality Improvement in Primary Care implementation. It was a descriptive and exploratory research, with qualitative approach, developed in the municipalities belonging to the 19th Regional Health Coordination of the state. The participants were 24 municipal health managers. Data collection was performed from January to May 2017 through a semi- structured interview. For the evaluation of the data was used the Thematic Content Analysis proposed by Minayo. The recommendations set forth in Resolution 466/2012 of the National Health Council were followed, respecting the regulatory norms of research involving human beings. There was an expressive contribution of female managers, older than 40 years. It was highlighted the value of the experience in the position and higher education; however, still it is necessary to advance in the incentive to formation in health area. The inclusion of health managers in charge through a political party, allied to the challenges faced in the current conjuncture of the country has a direct impact on health actions and services. It was pointed out the creation of a link between the managers and the local space in order to strengthen the common alliances of the organizational reality. The program was considered a real and palpable possibility to reorganize the work process of the teams and to establish links with the users from the local reality. Improvement of access was identified through the ambience, embracement and adequacy of the physical structure. The qualification of the health professionals was valued; however, the institutional support through actions of permanent education is still incipient. In addition, the program's ability to reflect the reality of teams was questioned. The perception of the managers about the program involved subjective and objective aspects related to the role of management in the process of primary care qualification. It was pointed out that the municipal and state administrations bet and stimulate processes of permanent education in the teams, linking to the strategies of institutional support to face the difficulties pointed out.